Unusual cause of gas complicating a biloma, postcholecystectomy. Issue 4 (15th April 2021) - Spence, Cameron; Ahmad, Fatima; Bolton, Louisa; Parekh, Amit
Abstract : A 50-year-old man presented to the emergency department with abdominal pain, vomiting and fever. He had been admitted 6 months ago with acute cholecystitis when he underwent endoscopic retrograde cholangiopancreatography (ERCP) to remove ductal gallstones. Elective cholecystectomy was performed 3 days prior to the current admission. CT demonstrated a fluid and gas containing collection in the gallbladder fossa, biliary gas and free intra-abdominal gas. ERCP revealed a retained common bile duct gallstone and leakage from the cystic duct remnant. We postulate that the gas within the collection originated from intrahepatic gas post-ERCP or from a gas forming organism. The free intra-abdominal gas originated from the collection rather than an intraoperative bowel injury. This complicated case highlights an unusual appearance of a common complication. It demonstrates the importance of discussion with the clinical team to ensure that an accurate diagnosis is made and the correct treatment is provided.